CITATION OF THE SCIENTIFIC PRODUCTIVITY OF CHEMISTS IN CHILE - Bernabe L Rivas; Daniel A. Palacio (Journal of the Chilean Chemical Society, 2020)
It is very relevant give the scientific productivity to the world scientific community as well as to the society. One of the most common and important media is through published papers in Journals recognized for different international sources and also measured by the impact factor. One the last factor has been the Hirsh index or H-index. The current contribution gives information of the chemists in Chile with H-index higher or equal 20 with respect to the self- citation (T) according to the recent publication.